Kazimierz Łaski and the scope and significance of the price mechanism - Jan Toporowski (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
Kazimierz Łaski's first contributions to economics were on the theory of growth and equilibrium in the socialist economy. He gravitated in between Włodzimierz Brus, who argued that the economy could be brought into equilibrium through market mechanisms, and the most profound influence on Łaski, Michał Kalecki. In Kalecki's view, the socialist economy is brought into equilibrium by means of investment and an appropriate wage policy, determined by central planners. Markets and price mechanisms cannot bring about general equilibrium but function to distribute profits among enterprises in the economy. With cost minimisation, markets and prices in socialism, if left to themselves, generate similar deflationary tendencies to the ones that obtain under capitalism. The scope and significance of the price mechanism thus goes beyond its rather trivial application to market equilibrium.
Keywords: B24; B31; D59; E11; P21; P22; 330; market socialism; central planning; price equilibrium; Kalecki; Łaski; Brus